Analysis of Ki-67 expression in oral premalignant lesions and normal oral mucosa: An immunohistochemical study - Basheer H Beevi; Suhas Ramananda Nayak; Celestina D Peter; Ajay K Haridas; Lin Jacob; Asaf Aboobakker (Wolters Kluwer Medknow Publications, 2019)
Aim: This study aimed to evaluate the Ki-67 expression in oral premalignant lesions and normal oral mucosa. Materials and Methods: The cases were selected on the basis of the details obtained from the patients. A total of 45 specimens were divided into three groups: Group 1 (normal mucosa), Group 2 (clinically and histologically diagnosed as oral lichen planus), and Group 3 (clinically and histologically diagnosed as leukoplakia). Specimens were prepared and the slides for Ki-67 were observed under light microscope with a magnification of ×400. The tissue samples were thoroughly examined, and the pattern of expression was analyzed semiquantitatively by counting the number of positive cells. Results: The mean positive cell count of normal mucosa was 23.20±2.89, of oral lichen planus was 42.82±2.65, and of leukoplakia was 82.14±3.10. There was a statistically significant difference of expression observed between the groups (P < 0.001). On multiple comparisons using Tukey post hoc test, a statistical difference was found between all the three groups. Conclusion: Ki-67 is an easily applicable marker of cell proliferation whose expression correlates well with the disease progression.